Experimental Investigation of Local Exhaust Ventilation Effectiveness at Welding Laboratory - Ngali, Alexta Baring; Mustaffa, Norrizal (Progress in Engineering Application and Technology, 2023)
The purpose of this research is to measure the LEV critical parameters according to DOSH standard requirements and follow the guidelines as stated in the American Conference of Governmental Industrial Hygienists (ACGIH). The experiment is conducted at the welding laboratory, Fakulti Kejuruteraan Mekanikal dan Pembuatan (FKMP), UTHM. The apparatus for conducting the experiment is a tachometer, a pitot tube, and an anemometer. The device is used to determine the velocity pressure, static pressure, total pressure, and speed in evaluating the effectiveness of the LEV system. Based on the data obtained, the results for face velocity on all hoods are very satisfactory and above the minimum required rate of 100 fpm. However, for capture velocity results, only four out of 14 hoods achieved the minimum required rate of 100 fpm from 8-inch distances. Meanwhile, the results obtained from the hoods at 16 and 24 inches from the worktable did not achieve the minimum level required. For velocity measurements on the ducting section of the LEV system, only one of the nine data measurement points did not reach the minimum required rate of 2000 fpm. The location of the intended point is at point 1, where the results of the data taken are not satisfactory. In conclusion, the efficiency of the LEV system is not satisfactory, following the results for capture velocity and ducting section, which not achieve the standard required. However, this system still works, especially to remove welding fumes.